EFEK PELATIHAN KEMAMPUAN PENYUSUNAN PERANGKAT PERCOBAAN SAINS UNTUK OPTIMALISASI CTL - Istiyono, Edi; Wilujeng, Insih (Universitas Negeri Yogyakarta, 2004)
Activity of service community have objects: (1) after upgrading, partie Sainsnts have a skill to use of science equipment needed of CTL, (2) partie Sainsnts have a skill to use, plan, and make science equipment needed of CTL, (3) partie Sainsnts have a skill to complete the equipment with work sheet, (4) partie Sainsnts have a skill to make science equipment from second-hand materialThe activity is explaining, information-discussion, work group,workshop and experiment. The activity is carried out classical and group for24 hour. The activity is explaining, discussion, topic choosing that are continued work group and presentation.Based on observation can be concluded: (1) increase of skill to use of science equipment needed of CTL, (2) increase of skill to use, plan, and make science equipment needed of CTL, (3) particSainsnts have made science equipment completed with work sheet, and (4) particSainsnts have had a skill to make science equipment from second-hand material.